2019
DOI: 10.1101/788422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ictal recruitment of anterior nucleus of thalamus in human focal epilepsy

Abstract: The thalamic nuclei play diverse roles in the initiation, propagation, and termination of temporal lobe seizures. The role of the anterior nucleus of the thalamus (ANT) -a node that is integral to the limbic network is unclear. The objective of this study was to characterize temporal andspectral patterns of ANT ictal recruitment in drug-resistant temporal lobe epilepsy (TLE). We hypothesized that seizures localized to the temporolimbic network are likely to recruit ANT, and the odds of recruitment were higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…A further study by Toth et al . 98 used an epileptogenicity index based on SEEG data and found that seizures that had an onset in the mesial temporal lobe (compared with other SOZs) had a higher and faster rate of ANT recruitment and that ANT recruitment preceded clinical onset. They also found that seizures that recruited the ANT lasted longer.…”
Section: Propagation Points Within the Epileptogenic Networkmentioning
confidence: 99%
“…A further study by Toth et al . 98 used an epileptogenicity index based on SEEG data and found that seizures that had an onset in the mesial temporal lobe (compared with other SOZs) had a higher and faster rate of ANT recruitment and that ANT recruitment preceded clinical onset. They also found that seizures that recruited the ANT lasted longer.…”
Section: Propagation Points Within the Epileptogenic Networkmentioning
confidence: 99%
“…Here, we present a freely-available open-source toolbox that was designed to carry out neuroimaging-based DBS research on a group level. Although our own development focused on patients undergoing DBS with chronicallyimplanted electrodes, Lead group was recently used to localize stereotactic intracranial EEG (iEEG) electrodes as well (Toth et al, 2019).…”
Section: Discussionmentioning
confidence: 99%